2007
DOI: 10.1002/ajh.21096
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis and monitoring in the clinical management of patients with chronic myelogenous leukemia treated with tyrosine kinase inhibitors

Abstract: The well-established molecular pathogenesis of chronic myelogenous leukemia (CML) and its consequences for laboratory testing and clinical management illustrate a classic paradigm for the importance of molecular diagnostics in targeted drug therapy. The success of the tyrosine kinase inhibitor (TKI), imatinib, as the currently recommended first-line treatment of early chronic phase CML has both fueled the need for timely and reproducible molecular testing of the BCR-ABL1 fusion transcript in diagnosis and moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…Cytogenetic study and qualitative RT-PCR have prime importance at the time of diagnosis, whereas serial quantitative RQ-PCR is recommended for therapeutic monitoring45.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytogenetic study and qualitative RT-PCR have prime importance at the time of diagnosis, whereas serial quantitative RQ-PCR is recommended for therapeutic monitoring45.…”
Section: Discussionmentioning
confidence: 99%
“…CML patients with breakpoint in micro bcr (μ-bcr), e19a2 and p230 chimeric protein, may demonstrate prominent neutrophilic and/or thrombocytosis; these should not be diagnosed as chronic neutrophilic leukaemia (CNL) or essential thrombocythaemia (ET)1. Therefore, in the current scenario cytogenetic and molecular analyses of CML patients have become mandatory in order to undertake diagnostic evaluation and monitor/predict response to newer molecular targeted treatment modalities like imatinib mesylate (IM)1–5. Variable frequencies of BCR-ABL fusion transcripts have been reported from different parts of the world26–11; a few documented b2a2 to be more common78, whereas other studies found b3a2 to be more common9–11.…”
mentioning
confidence: 99%
“…This translocation - ABL gene (chromosome 9) and BCR gene (chromosome 22) - originates a BCR-ABL fusion gene, leading to the expression of a chimeric BCR-ABL protein with tyrosine-kinase activity [13-15]. The most commonly used procedures for the initial diagnosis and management of CML patients are expensive and time consuming, e.g karyotype analysis, reverse transcriptase polymerase chain reaction analyses (RT-PCR) and fluorescence in-situ hybridization (FISH) [16-18]. Therefore, there is a need for molecular methods able to detect and quantify the BCR-ABL fusion transcripts, which is of paramount relevance when monitoring minimal residual disease and genetic recurrence in patients known to harbor the translocation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…2 Allied to its diagnostic utility, molecular analysis is central to contemporary classification and prognostic assignment, 3,4 and it is particularly well suited to testing for minimal residual disease after therapy. 5,6 A variety of molecular phenomena are amenable to routine diagnostic molecular analysis, with an assessment of gene rearrangements currently being the most commonly evaluated phenomenon. Gene rearrangements can be conveniently grouped into two broad categories: physiological and pathological.…”
Section: The Basics Of Diagnostic Molecular Hematopathologymentioning
confidence: 99%